Influence of the bed joint thickness on the bearing capacity of the brick masonry under compression loading: an ultrasound assessment - Monteagudo, Silvia M.; Casat, María Jesus; Gálvez, Jaime C. (Revista de la Construcción. Journal of Construction, 2015)
The aim of this paper is to analyse the influence of mortar bed joint thickness on the structural behaviour of brick-masonry specimens under compressive stress. Moreover, the progressive cracking of the material was studied during the loading process. Nine walls and nine columns were tested, combining three mortar bed joint thicknesses. Simultaneously, ultrasound, extensometer and Schmidt hammer measurements were recorded. The obtained results show that the thinner the mortar bed joint (5mm), the greater the breaking load (20.5N/mm2) and ultrasonic pulse speed. In addition, ultrasound evaluation shows good agreement with the extensometer measurements and allows accurate detection of the inner material failure.